1992
DOI: 10.1002/star.19920440105
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Degradability of Starch by Gelatinization Enthalpy as Measured by Differential Scanning Calorimetry

Abstract: It was investigated whether the degradability of starch could be predicted by differential scanning calorimetry (DSC). Degradation of potato starch with a varying degree of gelatinization. of isolated starch of different origins, and of raw materials differing in origin and technological treatment was determined with α‐amylase and bovine ruminal fluid. Gelatinization enthalpy and the gelatinization temperature of starch were determined by DSC. There was a good correlation between gelatinization enthalpy measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It has been proposed that there is an inverse relationship between a-amylase activity and gelatinization enthalpy in starch granules (Wolters and Cone 1992). Although enthalpy did not significantly change from brown rice to different germination durations for both cultivars, there were significant differences when comparing different germination durations within each cultivar.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been proposed that there is an inverse relationship between a-amylase activity and gelatinization enthalpy in starch granules (Wolters and Cone 1992). Although enthalpy did not significantly change from brown rice to different germination durations for both cultivars, there were significant differences when comparing different germination durations within each cultivar.…”
Section: Resultsmentioning
confidence: 79%
“…These differences in enthalpy between cultivars and between ger-mination durations may be related to the extent of starch hydrolysis. It has been proposed that there is an inverse relationship between a-amylase activity and gelatinization enthalpy in starch granules (Wolters and Cone 1992). Hydrolysis of the amorphous lamellae may increase gelatinization enthalpy in Wells and Jupiter at the beginning of germination.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the affinity of starch degrading enzymes may be different for PS, as PS is difficult to digest with pancreatic enzymes and enzymes from other origin (Cone, 1991). Differences in degradation of starch are mainly caused by differences in level of unsealing, so by differences in the physical properties of the macromolecules (Wolters and Cone, 1992) and not by differences in the chemical composition (Cone et al., 1992). Although layers of protein and lipids around the starch molecules may be present in some starch sources (Cone, 1991) this is not determinative for the degree of degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have previously reported the use of DSC to study starch gelatinization [28][29][30]. Gelatinization endotherm obtained by DSC is an overall measurement of the progressive loss of long, medium and short-range order in starch granules as they are heated in excess water.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%